KEUNGGULAN KOMPARATIF DAN KOMPETITIF TANAMAN PANGAN DI SENTRA PRODUKSI PAPUA (Studi Kasus Kabupaten Jayapura) - Malik, Afrizal (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2008)
The assesment study aimed to determine the characteristics of farming system, comparative advantage, competitiveness of farmes practices and to study potential crops which suitable to be developed in Jayapura Regency.